The intention to purchase plant-based meat among generation Y in Malaysia - Yap, Wai Hoong (2023)
The objective of this research was to investigate the factors that influence the intention to purchase plant-based meat among Generation Y in Malaysia. To achieve this objective, the study employed the Theory of Planned Behavior (TPB) as a theoretical framework and examined the impact of five independent variables: attitude, subjective norms, perceived behavioral control, food safety, and environmental concern on the purchase intention of plantbased meat. The target respondents for this study were Generation Y in Malaysia. A total of 384 sets of survey questionnaires were collected to gather data for analysis. The Statistical Package for the Social Sciences (SPSS) software was utilized to assist in the analysis of the collected data. The data analysis involved examining the demographic profile distribution, conducting a reliability test, using Q-Q plots, calculating Pearson's correlation coefficient, performing multiple regression, conducting ANOVA, assessing variance inflation factor (VIF), and analyzing t-statistics. The results of the analysis indicated that all five independents variables had a significant influence on the purchase intention of plant-based meat among Generation Y in Malaysia. These findings suggest that the five independent variables are important factors in shaping the intention to purchase plant-based meat among this demographic. The study also highlights the limitations and offers recommendations for future researchers, marketers, and policymakers to improve the adoption of plant-based meat in Malaysia.